2014
DOI: 10.1074/mcp.m113.028480
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Oxidative Stress and Mitochondrial Dysfunctions to Spontaneous Culture Degeneration in Aspergillus nidulans

Abstract: Filamentous fungi including mushrooms frequently and spontaneously degenerate during subsequent culture maintenance on artificial media, which shows the loss or reduction abilities of asexual sporulation, sexuality, fruiting, and production of secondary metabolites, thus leading to economic losses during mass production. To better understand the underlying mechanisms of fungal degeneration, the model fungus Aspergillus nidulans was employed in this study for comprehensive analyses. First, linkage of oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 89 publications
5
49
0
Order By: Relevance
“…Increasing evidence has suggested that oxidative damage may be a key factor of ageing in species ranging from C. elegans to Drosophila to humans (Stadtman, ; Wallace, ; Finkel and Holbrook, ; Hekimi and Guarente, ). Furthermore, oxidative stress can also cause fungal degeneration, resulting in several changes, including the overgrowth of hyphae, formation of sectors and reduced sporulation and virulence (Li et al ., ). In the HIGS plants, ROS were significantly accumulated and caused damage to Pst .…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence has suggested that oxidative damage may be a key factor of ageing in species ranging from C. elegans to Drosophila to humans (Stadtman, ; Wallace, ; Finkel and Holbrook, ; Hekimi and Guarente, ). Furthermore, oxidative stress can also cause fungal degeneration, resulting in several changes, including the overgrowth of hyphae, formation of sectors and reduced sporulation and virulence (Li et al ., ). In the HIGS plants, ROS were significantly accumulated and caused damage to Pst .…”
Section: Discussionmentioning
confidence: 97%
“…Strain H915-1 is an industrial producer, which was generated through several round of compound mutation, whereas strains L2 and A1 are the degenerated isolates of A. niger H915-1 during subsequent culture, as filamentous fungi frequently and spontaneously degenerate during maintenance in artificial media due to chromosome instability9. Escherichia coli JM109 was used as a host for recombinant DNA manipulation.…”
Section: Methodsmentioning
confidence: 99%
“…Role for Pfma pathway in UV protection of spore Fungal melanins frequently play important roles in cell protection including UV resistance and stresses (Eisenman and Casadevall, 2012;Li et al, 2014). To test the UV resistance of non-pigmentation mutants, we performed spore germination experiments under different UV exposure doses to WT, and DPfmaE mutants (EXPERIMENTAL PROCEDURES).…”
Section: Scytalone Restores the Conidial Pigmentation Of A Dpfmae Strainmentioning
confidence: 99%